Porphyrin-lipid nanovesicles (Porphysomes) are effective photosensitizers for photodynamic therapy - Guidolin Keegan; Ding Lili; Chen Juan; Wilson Brian C.; Zheng Gang (Nanophotonics, 2021)
Porphysomes (PS) are liposome-like nanoparticles comprising pyropheophorbide-conjugated phospholipids that have demonstrated potential as multimodal theranostic agents for applications that include phototherapies, targeted drug delivery and in vivo fluorescence, photoacoustic, magnetic resonance or positron emission imaging. Previous therapeutic applications focused primarily on photothermal therapy (PTT) and suggested that PSs require target-triggered activation for use as photodynamic therapy (PDT) sensitizers. Here, athymic nude mice bearing subcutaneous A549 human lung tumors were randomized into treatment and control groups: PS-PDT at various doses, PS-only and no treatment negative controls, as well as positive controls using the clinical photosensitizer Photofrin. Animals were followed for 30 days post-treatment. PS-PDT at all doses demonstrated a significant tumor ablative effect, with the greatest effect seen with 10 mg/kg PS at a drug-light interval of 24 h. By comparison, negative controls (PS-only, Photofrin-only, and no treatment) showed uncontrolled tumor growth. PDT with Photofrin at 5 mg/kg and PS at 10 mg/kg demonstrated similar tumor growth suppression and complete tumor response rates (15 vs. 25%, p = 0.52). Hence, porphysome nanoparticles are an effective PDT agent and have the additional advantages of multimodal diagnostic and therapeutic applications arising from their intrinsic structure. Porphysomes may also be the first single all-organic agent capable of concurrent PDT and PTT.